The Importance of “Soft Skills” in the Formation of a Modern Specialist (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
In the rapidly evolving professional landscape, technical expertise alone is no longer sufficient for success. "Soft skills," such as communication, teamwork, adaptability, and emotional intelligence, play a crucial role in shaping a well-rounded modern specialist. These skills enhance professional interactions, foster collaboration, and improve problem-solving abilities. Employers increasingly value candidates with strong soft skills, as they contribute to workplace efficiency, leadership potential, and overall career growth. This paper explores the significance of soft skills in professional development and emphasizes their integration into educational and training programs to prepare specialists for the demands of the modern workforce.